Is percutaneous cholecystostomy bridge to cholecystectomy or definite therapy in high-risk patients with severe acute calculous cholecystitis? (Annals of Medical Research, 2021)
Aim: The medical records of 68 patients diagnosed with severe ACC and treated with PC at Başkent University Faculty of Medicine, General Surgery Clinic between January 2011 and January 2018 were retrospectively analyzed.Results: Among patients who underwent PC for severe ACC at our clinic, 39 (57.4%) were male. Their mean age was 71.7 (28-94) years. All patients had pain; 13 (19.1%) patients had nausea-vomiting; 8 (11.8%) had had fever. The mean time from symptom onset to hospital admission was 6.2 (1-30) days; the mean time from admission to PC placement was 2.1 (1-9) days. Twelve (17.6%) patients had minor complications due to cholecystostomy catheter. Twenty seven (39.7%) patients underwent cholecystectomy with a mean of 83.1 (20-705) days after cholecystostomy placement. Seventeen of these patients underwent laparoscopic surgery and 3 of them converted to open surgery. In 5 of 41 patients who did not undergo cholecystectomy, AC recurrence developed (12.2%) and PC was inserted again. Five (7.4%) patients died.Conclusion: Percutaneous cholecystostomy catheter is an effective treatment to control inflammation until cholecystectomy among high-risk patients diagnosed with severe cholecystitis and may be a definitive therapy for patients unable to undergo surgery.
Keywords: Acute cholecystitis; percutaneous drainage; cholecystostomy